In vitro Evaluation of Calcium Phosphate Precipitation on Possibly Bioactive Titanium Surfaces in the Presence of Laminin - Kostas Bougas; Victoria Franke Stenport; Fredrik Currie; Ann Wennerberg (Stilus Optimus, 2011)
Objectives: The aim of the present study was to evaluate calcium phosphate precipitation and the amount of precipitated protein on three potentially bioactive surfaces when adding laminin in simulated body fluid.Material and Methods: Blasted titanium discs were prepared by three different techniques claimed to provide bioactivity: alkali and heat treatment (AH), anodic oxidation (AO) or hydroxyapatite coating (HA). A blasted surface incubated in laminin-containing simulated body fuid served as a positive control (B) while a blasted surface incubated in non laminin-containing simulated body fuid served as a negative control (B-). The immersion time was 1 hour, 24 hours, 72 hours and 1 week. Surface topography was investigated by interferometry and morphology by Scanning Electron Microscopy (SEM). Analysis of the precipitated calcium and phosphorous was performed by Energy Dispersive X-ray Spectroscopy (EDX) and the adsorbed laminin was quantified by iodine (125I) labeling.Results: SEM demonstrated that all specimens except for the negative control were totally covered with calcium phosphate (CaP) after 1 week. EDX revealed that B- demonstrated lower sum of Ca and P levels compared to the other groups after 1 week. Iodine labeling demonstrated that laminin precipitated in a similar manner on the possibly bioactive surfaces as on the positive control surface.Conclusions: Our results indicate that laminin precipitates equally on all tested titanium surfaces and may function as a nucleation center thus locally elevating the calcium concentration. Nevertheless further studies are required to clarify the role of laminin in the interaction of biomaterials with the host bone tissue.